PENGARUH KETERAMPILAN GURU DALAM MEMBIMBING DISKUSI KELOMPOK KECIL TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VIII SMP NEGERI 4 LOGAS KECAMATAN LOGAS TANAH DARAT - Desia Rama Engla; Sopiatun Nahwiyah; Andrizal Andrizal (Universitas Islam Kuantan Singingi, 2023)
This study aims to determine the effect of teacher skills in guiding small group discussions on students' interest in learning and the factors that influence it in Islamic Education and Character Class VIII Subjects at SMP Negeri Logas, Logas Tanah Darat. Based on the results of data collection by means of observation, questionnaires, tests, interviews and documentation, then analyzed the data using a simple linear analysis formula and using SPSS 21.0 data, it can be concluded that: VIII in the field of PAI and Budi Pekerti studies at SMP Negeri 4 Logas, Logas Tanah Darat, is the value of the coefficient of determination (R square) of 0.174 (is the square of the correlation coefficient, or 0.174 x 0.174 = 0.0302). The magnitude of the coefficient of determination (R square) is 0.0302 while the rest is influenced by other variables while the factors that affect the Skills of Teachers in Guiding Small Group Discussions on Students' Interest in Learning in Islamic Education and Character as stated by one of the students are students who are less enthusiastic, especially children who are always vacuumed in learning, rarely speak during discussions, always rely on friends who are active but don't want to talk themselves, then the level of intelligence of students in understanding the material presented the teacher and the level of learning motivation possessed by the students themselves which depend also on the strategies and methods used by the teacher in PAI learning